2021
DOI: 10.1002/aelm.202001006
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Deformable Circuit Components with Liquid Metal

Abstract: Deformable electronics, specifically those incorporating liquid metal, allow for previously inaccessible mechanical behavior and exciting new technologies. This is demonstrated by recent, promising advances in the fabrication, characterization, device performance, and applications of liquid metal electronics. Through the use of liquid metals and soft, stretchable materials, it is shown that devices that provide stretchability and improved safety and comfort between humans and machines can achieve comparable or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 189 publications
(217 reference statements)
0
11
0
Order By: Relevance
“…Tensile strain, as described by the tensile modulus, is common to stretchable electronic material applications such as stretchable batteries, device interconnects, composite fibers, and electrodes in addition to physiological sensors. ,, The tensile modulus of the barium titanate composites with galinstan concentrations of 0, 10, and 30 vol % is shown in Figure a. For barium titanate composites, there was little to no impact on the tensile modulus when increasing galinstan concentration from 0GaInSn to 10GaInSn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tensile strain, as described by the tensile modulus, is common to stretchable electronic material applications such as stretchable batteries, device interconnects, composite fibers, and electrodes in addition to physiological sensors. ,, The tensile modulus of the barium titanate composites with galinstan concentrations of 0, 10, and 30 vol % is shown in Figure a. For barium titanate composites, there was little to no impact on the tensile modulus when increasing galinstan concentration from 0GaInSn to 10GaInSn.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding how the multimaterial composites behave under compression is imperative as one of their primary material applications is for pressure sensing, which has been previously investigated using microchannels of liquid metal in a substrate , and dispersions of materials like carbon black or carbon nanotubes for capacitive pressure sensing. , The compressive modulus of the barium titanate composites with 0, 10, and 30 vol % galinstan is shown in Figure a. The impact of the increasing galinstan concentration differed based on barium titanate concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Several publications have reported that eGaIn can damage the AgNWs by dissolving the Ag materials . Previous research showed that graphene, which is an sp 2 -bond-based carbon material, can prevent Ag dissolution. , In addition, a spray-coated multilayer of SWCNTs on AgNWs or nanoparticles (NPs) has been reported to provide an adequate physical and chemical barrier, protecting AgNWs and NPs from the reaction with eGaIn. Figure c shows the effect of using ACLM electrodes on luminance performance. Both had AgNW/SWCNT electrodes as the top electrode.…”
Section: Resultsmentioning
confidence: 99%
“…170 Sensors are powered by LMPCs based on thermoelectric generators (TEGs) or triboelectric nanogenerators (TENGs). [171][172][173] For example, Pan et al 174 fabricated a self-powered sensor using LMPC that collects energy from body movement through the TENG to power a digital humidity thermometer (Fig. 11f).…”
Section: Soft Sensorsmentioning
confidence: 99%